Advantage of tacrolimus/mycophenolate mofetil regimen for cytotoxic T cell‐mediated defence and its inhibition by additive steroid administration in high‐risk liver transplant recipients. (11th January 2016) - Uemoto, S.; Ozawa, K.; Kaido, T.; Mori, A.; Fujimoto, Y.
Summary: Our previous work revealed that the recipients with the highest pre‐existing numbers of CD8 + effector T cells (TE ) [hyperparathyroidism (HPT)E recipients] occupied approximately 30% of adult transplant recipients performed in our hospital. HPTE recipients demonstrated very poor clinical outcome compared with the remaining 70% of recipients with the lowest pre‐existing TE (LPTE recipient). This study aimed to clarify the best combined immunosuppressive regimen related to function of cytotoxic T lymphocytes (CTLs) for HPTE recipients. Eighty‐one HPTE recipients were classified into three types, according to the immunosuppressive regimens: type 1, tacrolimus (Tac)/glucocorticoid (GC); type 2, Tac/mycophenolate mofetil (MMF)/GC; and type 3, Tac/MMF. Frequencies of severe infection, rejection and hospital death were the highest in types 1 and 2, whereas the lowest occurred in type 3. The survival rate in type 3 was the highest (100%) during follow‐up until post‐operative day 2000. Regarding the immunological mechanism, in type 1 TE perforin and interferon (IFN)‐γ were generated through the self‐renewal of CD8 + central memory T cells (TCM ), but decreased in the early post‐transplant period due to marked down‐regulation of interleukin (IL)‐12 receptor beta‐1 of TCM. In type 2, the self‐renewal TCM did not develop, and the effector function could not be increased. In type 3, in contrast, the effectors and cytotoxicity were correlated inversely with IL‐12Rβ1 + TCM levels, and increased at the highest level around the pre‐transplant levels of IL‐12Rβ1 + TCM . However, the immunological advantage of Tac/MMF therapy was inhibited strongly by additive steroid administration.